1,1-Diethyl-3-(4-methoxybenzoyl)thiourea - Al-Abbasi, Aisha A.; Mohamed Tahir, Mohamed Ibrahim; Kassim, Mohammad (International Union of Crystallography, 2011)
In the title compound, C13H18N2O2S, the 4-methoxybenzoyl fragment is approximately planar [maximum deviation = 0.057 (2) Å] and twisted relative to the thioamide fragment, forming a dihedral angle of 86.62 (6)°. The two Csp 2—Nsp 2 bonds in the thiourea unit differ significantly in length [1.327 (2) and 1.431 (2) Å]. In the crystal, N—H(...)O hydrogen bonds link the molecules into chains parallel to [010].